PENGARUH FIRM SIZE, FINANCIAL RISK TERHADAP VALUE OF THE FIRIM DENGAN EARNING MANAGEMENT SEBAGAI VARIABEL INTERVENING DAN CSRD SEBAGAI VARIABEL MODERASI: indonesia - hasyim, abdul malik (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2024)
This research aims to find out empirical evidence of the influence of the independent variables GCG (X1), Capital (X2), Firm Size (X3), Financial Risk (X4), mediating variable (Z1), Value of the Firm Y attachment variable, and CSRD moderating variable (Z2) BPD banks registered with OJK 2019 - 2023. The data analysis method uses Smar PLS 3. The results of the analysis using PLS to obtain results show that GCG has a negative effect on earnings management. GCG has a positive effect on company value, Capital has a positive effect on Profit Management, Capital has a negative effect on company value, Company size has a negative effect on earnings management, Company size has a positive effect on company value, Financial Risk has a positive effect on earnings management, Financial risk has a positive effect on company value, earnings management has a positive effect on company value and CSRD has a positive effect on company value. The results obtained from the indirect effect significance test were that GCG had a negative effect on company value through earnings management, company size had a negative effect on company value through earnings management. Financial risk has a positive effect on company value through earnings management. Capital has a positive effect on company value through earnings management. CSRD can moderate the influence of GCG on company value. CSRD cannot moderate the influence of company size on company value, CSRD cannot moderate the influence of financial risk on company value. CSRD can moderate the influence of capital on company value.